TOBACCO TAX INCREASE BLOWS UP ON LEGISLATORS - TROY,FC (Tufts Archival Research Center, 2007)
Newspaper article from NY local paper. Explores alternative cheaper sources of cigarettes in light of the raised cigarette tax. Offers cost comparison between local and Native American shops. Criticizes the tax increase and deems it ineffective.